2016
DOI: 10.1103/physrevb.93.184409
|View full text |Cite
|
Sign up to set email alerts
|

Long-range and short-range magnetic correlations, and microscopic origin of net magnetization in the spin-1 trimer chain compoundCaNi3P4O14

Abstract: Spin-spin correlations and microscopic origin of net magnetization in the spin-1 trimer chain compound CaNi3P4O14 have been investigated by powder neutron diffraction. The present study reveals a three dimensional long-range magnetic ordering below 16 K where the magnetic structure consists of ferromagnetic trimers that are coupled ferromagnetically along the spin-chain direction (b axis). The moment components along the a and c axes arrange antiferromagnetically. Our study establishes that the uncompensated m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 47 publications
6
18
0
Order By: Relevance
“…The presence of weak gapless magnetic excitations that persist up to ~ 100 K, is consistent with the previous neutron diffraction study [22] which revealed 1D short-range spin-spin correlations at T > T C .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The presence of weak gapless magnetic excitations that persist up to ~ 100 K, is consistent with the previous neutron diffraction study [22] which revealed 1D short-range spin-spin correlations at T > T C .…”
Section: Resultssupporting
confidence: 91%
“…The spin-chains in CaNi 3 P 4 O 14 are formed by edge-shared NiO 6 (Ni 2+ ; 3d 8 indicates the presence of short-range spin-spin correlations within the chains. Short-range spin-spin correlations were indeed found in neutron diffraction study as reported by us [22]. This may be noted that there are no phonon modes whose intensity increases with increasing temperature around the spin wave spectra.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Neutron-scattering technique can provide evidence not only for the presence of LRO AFM structure but also for short-range ordered (SRO) AFM clusters of spins in the CSG systems. The presence of SRO AFM spin clusters gives rise to diffuse scattering in the neutron-scattering patterns [46,74,[94][95][96][97][98]. Accordingly, we carried out NPD measurements on powder samples of CFN to obtain direct evidence for the presence of AFM spin clusters.…”
Section: F Direct Evidence For the Presence Of Spin Clusters In Cfn mentioning
confidence: 99%
“…As examples of works, we cite the uncovering of correlations in the flux-line lattice of a type II superconductor [2], the characterization of the spin ice state in Ho 2 Ge 2 O 7 [3], the determination of the structure of liquids [4,5], and the investigations of structural and magnetic short-range-correlations for a large variety of magnetic compounds; see example of recent works in Refs. [6][7][8].…”
Section: Introductionmentioning
confidence: 99%